Salar del Hombre Muerto, source of lithium-tolerant bacteria - Martínez, Fabiana Lilian (2020)
The Salar del Hombre Muerto is a flat salt with great microbial activity despite the existing extreme conditions like high altitude, lack of water, low level of oxygen, high radiation and high concentration of sodium and lithium chloride. Despite these unfavorable conditions, we found microbial diversity with the presence of fungi, algae, and bacteria. From aqueous solutions and soil samples, a total of 238 bacteria were isolated and 186 of them were able to grow in the presence of salt. About 30% of the strains showed the ability to grow in solid medium proximally to a LiCl solution close to saturation (636 g/L). These isolates were characterized taking into account the morphology, Gram stain, ability to form biofilms and to produce pigments, and mainly according to the tolerance against lithium chloride. Bacillus was predominant among the most tolerant 26 microorganisms found, followed by Micrococcus and Brevibacterium. Members of the genera Kocuria, Curtobacterium and Halomonas were also represented among the bacteria with tolerance to 30 and 60 g/L of LiCl in defined liquid medium. All the capacities found in these microorganisms make them extremely interesting for biotechnological applications.